Enhancing the shelf life of tomato ketchup: An organoleptic analysis of natural and synthetic preservatives (Indian Journal of Arid Horticulture, 2025)
Tomato ketchup, a widely consumed condiment, requires effective preservation to maintain its shelf-life, taste, and quality. This study, conducted in 2025 at ICAR-KVK Panchmahal, Gujarat, compared the sensory attributes of tomato ketchup prepared with natural preservatives (NP) (vinegar and lemon juice) and synthetic preservatives (SP) (sodium metabisulphite). Sensory evaluation was conducted using a 5 point Hedonic scale among 40 farmers and 10 staff members of ICAR-KVK Panchmahal, Gujarat. The organoleptic assessment revealed that colour was slightly more preferred in SP ketchup, with 76% of respondents strongly liking it, compared to 74% for NP ketchup. Flavour and smell were rated higher for NP ketchup, with 72% and 84% of respondents strongly liked its flavour and aroma, respectively, while SP ketchup scored 68% and 80% on these parameters. Texture preference was comparable, with 52% of respondents strongly liking NP ketchup and 50% preferring SP ketchup, though the Weighted Mean Score (WMS) was higher for SP ketchup (4.26) than NP ketchup (4.12). General acceptability was higher for SP ketchup (WMS: 4.68) compared to NP ketchup (4.52), primarily due to its extended shelflife (40 days at room temperature, 90 days refrigerated vs. 7 and 15 days for NP). NP ketchup was favoured for its natural taste. Production costs were lower for SP ketchup (₹92/kg) than NP (₹130/kg), though NP appeals to health-conscious consumers. While SP ketchup offers superior shelf stability and cost-effectiveness, NP ketchup is preferred for its flavour and natural ingredients, highlighting a trade-off between shelf-life, cost and sensory appeal.